Decellularized Whole-Organ Pre-vascularization: A Novel Approach for Organogenesis - Fathi, Ibrahim; Imura, Takehiro; Inagaki, Akiko; Nakamura, Yasuhiro; Nabawi, Ayman; Goto, Masafumi (Frontiers in Bioengineering and Biotechnology, 2021)
INTRODUCTION. Whole-organ decellularization is an attractive approach for three-dimensional (3D) organ engineering. However, progress with this approach is hindered by intra-vascular blood coagulation that occurs after in vivo implantation of the re-cellularized scaffold, resulting in a short-term graft survival. In this study, we explored an alternative approach for 3D organ engineering through an axial pre-vascularization approach and examined its suitability for pancreatic islet transplantation. METHODS. Whole livers from male Lewis rats were decellularized through sequential arterial perfusion of detergents. The decellularized liver scaffold was implanted into Lewis rats, and an arteriovenous bundle was passed through the scaffold. At the time of implantation, fresh bone marrow preparation (BM; n=3), adipose-derived stem cells (ADSCs; n=4), or HBSS (n=4) was injected into the scaffold through the portal vein. After 5 weeks, around 2,600 islet equivalents (IEQs) had been injected through the portal vein of the scaffold. The recipient rats were rendered diabetic by the injection of 65 mg/kg STZ intravenously 1 week before islet transplantation and were followed up after transplantation by measuring the blood glucose and body weight for 30 days. Intravenous glucose tolerance test was performed in the cured animals, and samples were collected for immunohistochemical (IHC) analyses. Micro-computed tomography (CT) images were obtained from one rat in each group for representation. RESULTS. Two rats in the BM group and one in the ADSC group showed normalization of blood glucose levels, while one rat from each group showed partial correction of blood glucose levels. In contrast, no rats were cured in the HBSS group. Micro-CT showed evidence of sprouting from the arteriovenous bundle inside the scaffold. IHC analyses showed insulin-positive cells in all three groups. The number of von-Willebrand factor-positive cells in the islet region was higher in the BM and ADSC groups than in the HBSS group. The number of 5-bromo-2'-deoxyuridine-positive cells was significantly lower in the BM group than in the other two groups. CONCLUSIONS. Despite the limited numbers, the study showed the promising potential of the pre-vascularized whole-organ scaffold as a novel approach for islet transplantation. Both BM and ADSCs were superior to the acellular scaffold.